Designing a new high gain CMOS amplifier towards a 17.22 MHz MEMS based Si oscillator for a cost effective clock generator IC - Roy, S.; Ramiah, H.; Reza, A.W. (Institute of Electronics, Information and Communication Engineers (IEICE), 2015)
A novel sustaining amplifier is designed and characterized for a Si-based MEMS resonator, in implementing a reference oscillator in 180 nm CMOS process. A two port electrical model of the MEMS resonator is used to compute the insertion loss (-76 dB) and phase shift (95 degrees). Total open loop transimpedance gain is achieved as 122 dB Omega with -70 degrees phase shift, at the resonant frequency of 17.22 MHz. This amount of gain is investigated as capable to sustain MEMS resonator's oscillation, in the realization of a cost effective, miniaturized and low power CMOS reference oscillator which oversees on application in clock generation.